Between Bohemia and Suburbia : Boburbia in the USA - Weston, William J., 1960- (Abingdon, Oxon : Routledge, 2019)
This book identifies a distinctive kind of urban neighborhood that is on the rise throughout the USA, the dense, walkable, mixed-use bourgeois-bohemian suburb or the "boburb." Itlooks at case studies of areas to live in Louisville, Kentucky. Based on scores of interviews with college graduates, backed by survey data and Census figures, it provides a clear, historical account of how these spaces arose. Chapters depict, analyze, and compare the Highlands neighborhood with other Louisville boburbs, contrasting them with the ephemeral bohemian quarters and the many suburban subdivisions. The Highlands are also compared with five other boburbs around the USA. Attention is given to the influence of transportation systems in shaping residential, community, and commercial spaces. Deeper cultural reasons for choosing the boburbs or the suburbs are also explored, including the political "big sort" between liberal and conservative places, and Bourdieu's account of how the distinction between economic and cultural capital shapes how people choose to live where they live. This book will appeal to those interested in the evolution and distinctions among urban neighborhoods. It is ideal for academics and students within urban geography, urban gentrification, cities, and population.
OCLC-licensed vendor bibliographic record.
Keywords: SOCIAL SCIENCE / Sociology / Urban; Neighborhoods -- United States; Suburbs -- United States; SCIENCE / Earth Sciences / Geography